OP83 Comparing the impact of price change and mass media campaigns on reducing cardiovascular disease mortality and disparities in the US. (13th September 2016) - Pearson-Stuttard, J; Bandosz, P; Rehm, C; Afshin, A; Penalvo, J; Whitsel, I; Micha, R; Danaei, G; Gaziano, T; Conrad, Z; Lloyd-Williams, F; Mozaffarian, D; et al.
Abstract : Background: Cardiovascular disease (CVD) mortality burdens remain large and unequal in the US, and much is attributable to poor diets. Few data exist regarding the potential population level impact of policies aimed at improving dietary intake, and the effect on disparities through programmes such as the Supplemental Nutrition Assistance Programme (SNAP). We aimed to estimate reductions in CVD mortality and disparities achievable in the US population up to 2030 through food price changes and mass media campaign interventions targeting fruits and vegetables (F&V) and sugar sweetened beverages (SSBs). Methods: We developed a US IMPACT Food Policy Model to compare four contrasting food policy scenarios targeting dietary intake: a national F&V mass media campaign, F&V price reductions of 10% universally and 30% to SNAP participants, and a universal SSB price increase of 10%. Data sources included the National Vital Statistics System, SEER single year population estimates, the US Bureau 2012 National Population projections, and NHANES. We stratified the US population into SNAP participants, SNAP eligible (but not participating), and SNAP ineligible. We modelled cumulative deaths prevented or postponed (DPP) and life years gained (LYG) using best-evidence effect sizes for each policy including differential price elasticity estimates, existing mortality rates and trends, and F&V and SSB mortality effects. We stratified by age, sex, and CVD subtype from 2015 to 2030. Probabilistic sensitivity analyses were conducted with Monte Carlo simulation. Results: A universal 10% price reduction would yield the greatest national benefits, generating approximately 88, 000 DPPs (95% CI: 81, 000–94, 000) and 1, 369, 000 LYGs (1, 268, 000–1, 460, 000) by 2030. This compares with between 28, 000 (26, 000–30, 000) and 84, 000 (79, 000–89, 000) DPPs generated through a 1-year and 15-year MMC respectively. A 10% SSB price increase could yield approximately 29, 000 (25, 000–33, 000) DPPs, whilst a 30% F&V price reduction to SNAP participants only could reduce deaths by approximately 27, 000 (24, 000–30, 000). This scenario would reduce disparities the greatest, reducing CVD disparities by approximately 18% between SNAP participants and ineligible population. The other scenarios would have much lower effects upon disparities. Conclusion: All four dietary policies would be effective in reducing mortality. Reducing fruit and vegetable (F&V) price by 10% to the entire US would save most lives. However reducing F&V price by 30% to SNAP participants would reduce disparities the most, particularly if SNAP program coverage and penetration were improved. These results support population fiscal strategies targeting diet to reduce cardiovascular mortality and disparities in the US.